Analysis of the implementation of the Jakarta Marathon as a Sports Tourism event for the DKI Jakarta Province - Mohamat Emir Ferdian (Management Analysis Journal, 2023)
Sport Tourism which is routinely held in Jakarta almost every year is the Jakarta Marathon. This sports activity is very popular and in demand by the public both as participants and as spectators of these sports events both from local and foreign tourists and always contributes to increasing income in the tourism sector, especially in DKI Jakarta.The purpose of this study is important in order to realize the goal of developing sports tourism by analyzing its implementation which has reliable prospects to become the leading sector of sports tourism in DKI Jakarta.